2015
DOI: 10.1371/journal.ppat.1005230
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Characterization of the HCMV gH/gL/gO and Pentamer Cell Entry Complexes Reveals Binding Sites for Potently Neutralizing Human Antibodies

Abstract: Human Cytomegalovirus (HCMV) is a major cause of morbidity and mortality in transplant patients and in fetuses following congenital infection. The glycoprotein complexes gH/gL/gO and gH/gL/UL128/UL130/UL131A (Pentamer) are required for HCMV entry in fibroblasts and endothelial/epithelial cells, respectively, and are targeted by potently neutralizing antibodies in the infected host. Using purified soluble forms of gH/gL/gO and Pentamer as well as a panel of naturally elicited human monoclonal antibodies, we det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 47 publications
9
61
0
Order By: Relevance
“…This analysis revealed that the gH/UL116 complex has a boot-shaped structure similar to that of gH/gL. 3G16 and MSL-109 Fabs bind to the C-terminal domain and to the "heel" of the gH molecule, respectively, as previously described for gH/gL (54,72). Furthermore, the EM analysis and binding data (unpublished results) suggest that UL116 occupies a position similar to that of gL at the N-terminal end of gH (Fig.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…This analysis revealed that the gH/UL116 complex has a boot-shaped structure similar to that of gH/gL. 3G16 and MSL-109 Fabs bind to the C-terminal domain and to the "heel" of the gH molecule, respectively, as previously described for gH/gL (54,72). Furthermore, the EM analysis and binding data (unpublished results) suggest that UL116 occupies a position similar to that of gL at the N-terminal end of gH (Fig.…”
Section: Resultssupporting
confidence: 69%
“…We previously used single-particle negative-stain EM to characterize gH/gL, gH/gL/gO, and Pentamer complexes bound to neutralizing antibodies (54,72). Our data revealed that HCMV gH/gL has a boot-shaped structure similar to that of HSV-2 gH/gL (73) and that gO and the UL128/UL130/UL131A subunits bind to the N-terminal end of gH/gL in gH/gL/gO and Pentamer, respectively.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Possible explanations include a major role played by memory B cells of donor and recipient origins [122]. The gH/gL-pentamer complex represents the platform for prophylactic Pentamer-based vaccines of absolute interest [123,124].…”
Section: Vaccinesmentioning
confidence: 99%
“…Previous studies demonstrated that the PC comprises predominantly quaternary conformational epitopes that are formed by two or more subunits and in only rare cases epitopes that are constituted by single subunits of the PC (28,29). In addition, Ciferri et al identified amino acid residues that are either in close proximity to or part of conformational neutralizing epitopes within the PC (42). However, amino acid residues that constitute the minimal target sequence of a potent PC-specific NAb have not been described.…”
Section: Discussionmentioning
confidence: 99%